Autoimmunity and long-term safety and efficacy of alemtuzumab for multiple sclerosis: Benefit/risk following review of trial and post-marketing data. (April 2022) - Coles, Alasdair J; Jones, Joanne L; Vermersch, Patrick; Traboulsee, Anthony; Bass, Ann D; Boster, Aaron; Chan, Andrew; Comi, Giancarlo; Fernández, Óscar; Giovannoni, Gavin; Kubala Havrdova, Eva; LaGanke, Christopher; et al.
Does preexisting or treatment-emergent autoimmunity increase the risk of subsequent autoimmune disease in individuals with relapsing-remitting multiple sclerosis (MS) after alemtuzumab? In the extended phase 2/3 trials, 34/96 (35.4%) patients with and 395/1120 (35.3%) without preexisting autoimmunity developed non-MS autoimmunity. Thyroid autoimmunity after alemtuzumab courses 1 or 2 did not increase subsequent non-thyroid autoimmune adverse events. Therefore, autoimmune disease before or after alemtuzumab treatment does not predict autoimmunity after further courses, so should not preclude adequate alemtuzumab dosing to control MS. Finally, post-marketing safety data contribute toward a full record of the alemtuzumab benefit/risk profile for the MS field.